A new method for progressive collapse analysis of RC frames under blast loading - Shi Yanchao, Y.; Li, Z.; Hao, Hong (Pergamon, 2010)
The progressive collapse of structures under blast loading has attracted great attention all over the world. Some guidelines give specific procedures to analyse the progressive collapse of building structures. Numerical analysis and laboratory test results of the progressive collapse of structures have also been reported in the literature. Because the progressive collapse of a structure induced by blast loading occurs only after the blast-loading phase, most of these studies and guideline procedures perform progressive analysis by removing one or a few load-carrying structural members with static and zero initial conditions. The damage on adjacent structural members that might be induced by blast loads and the inevitable non-zero initial conditions when progressive collapse initiates are neglected. These simplifications may lead to inaccurate predictions of the structural collapse process. In this paper, a new method for progressive collapse analysis of reinforced concrete (RC) frame structures by considering non-zero initial conditions and initial damage to adjacent structural members under blast loading is proposed. A three-storey two-span RC frame is used as an example to demonstrate the proposed method. Numerical results are compared with those obtained using the alternative load path method, and with those from comprehensive numerical simulations by directly applying the blast loads on the frame. It is found that the proposed method with a minor and straightforward extension of the simplified 'member-removal' procedure is efficient and reliable in simulating the progressive collapse process of RC frame structures. It requires substantially less computational effort as compared to direct numerical simulations, and gives more accurate predictions of the structural progressive collapse process than the 'member-removal' approach.